The Role of The Mosque in Economic Empowerment and Community Welfare Through MSMEs in The South Jakarta Region - Imam Sofii; Indah Pertiwi (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: The purpose of this research is to map the various basic concepts of community empowerment to function mosques, actualize and develop socio-economic values. This research uses a qualitative research approach of participatory action research. namely interacting and socializing, so that it will improve capacity building and self-confidence from society. The research sites are Pondok Indah Grand Mosque and Jami’ Assakinah Mosque. The results of this study indicate that the role of the mosque in realizing the welfare of the community through UMKM is an actualization that is able to guarantee the economic independence of the community. It also helps the economic empowerment of the surrounding community, at the same time. The indicators found in these two mosques are the presences of professional and qualified personnel. They have the adequate infrastructure and strategic location surrounded by elite housing and offices. The mosque is easy to reach. Furthermore, it is close to objects that become empowerment, such as markets and street vendors. The economic empowerment of the mosque-based community was initiated by BMT, in order to optimize the function and role of the mosque as the center of civilization for the people and the economic welfare of the congregation or the community around the mosque. Besides that, it is also a strategy in order to empower the economy of the people by creating a Mosque Micro loan program (PMM). This program is designed for micro entrepreneurs who have difficulty obtaining or accessing capital. Keywords: mosque; economic empowerment; community welfare; UMKM